Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jdin.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and recommendations for clinical management of truncal acne from the Personalising Acne: Consensus of Experts panel

Abstract: Background: Truncal acne is common and burdensome for patients; however, there is paucity of evidence and guidance for the management of truncal acne. Currently, clinical practice guidelines provide very little guidance on the assessment or management of truncal acne.Objectives: To identify unmet needs in truncal acne and make recommendations to address clinical and management gaps using an international consensus.Methods: The Personalising Acne: Consensus of Experts panel consisted of 13 dermatologists, who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…25,26 Without this best-practice guidance, patients may receive suboptimal acne treatment, potentially resulting in higher psychological morbidity risk, physical scarring, and hyperpigmentation. 3,27,28 In current Asia-Pacific guidelines, topical retinoids are recommended as the first-line treatment for all acne severities, including as monotherapy for the treatment of comedonal acne and in combination with antimicrobials (including antibiotics and benzoyl peroxide [BPO]) for inflammatory acne lesions. 4,21,[24][25][26]29 Topical retinoids are thought to act by inhibiting the formation of microcomedones, mature comedones, and inflammatory lesions.…”
Section: Overview Of Current Published Guidelines In Asia-pacific Cou...mentioning
confidence: 99%
“…25,26 Without this best-practice guidance, patients may receive suboptimal acne treatment, potentially resulting in higher psychological morbidity risk, physical scarring, and hyperpigmentation. 3,27,28 In current Asia-Pacific guidelines, topical retinoids are recommended as the first-line treatment for all acne severities, including as monotherapy for the treatment of comedonal acne and in combination with antimicrobials (including antibiotics and benzoyl peroxide [BPO]) for inflammatory acne lesions. 4,21,[24][25][26]29 Topical retinoids are thought to act by inhibiting the formation of microcomedones, mature comedones, and inflammatory lesions.…”
Section: Overview Of Current Published Guidelines In Asia-pacific Cou...mentioning
confidence: 99%
“…These included encouraging healthcare professionals to prompt discussion about truncal acne, to grade truncal acne severity separately from facial acne, to individualize treatment based on impact of acne in different regions, and to consider risk for scarring. 29…”
Section: Clinical Data Supporting Use Of Trifarotene In Acnementioning
confidence: 99%
“…Despite the development of various assessment tools for truncal acne, the abovementioned tools are mostly used as tools for clinical research (Table 1). In real-world clinical practice, the investigator's global assessment (IGA), the Leeds visual severity scale, ECLA scales, and the comprehensive acne severity scale are widely used for assessing the severity of truncal acne [39]. Given the anatomical variations in acne, there are unmet needs to properly evaluate the severity of truncal acne in real-world clinical practice.…”
Section: Assessment Tool For Truncal Acnementioning
confidence: 99%
“…As the truncal regions are usually exposed in summer, there might be a seasonal variation in the burden of truncal acne. The consensus of an expert panel suggested that the visual analog scale (VAS) could be a useful tool for assessing the factors associated with the impact of disease on patients, and thereby help to identify the treatment goal for each patient [39].…”
Section: Psychosocial Burden Of Truncal Acnementioning
confidence: 99%
See 1 more Smart Citation